The influence of water resistance therapy on vocal fold vibration: a high-speed digital imaging study. (3rd July 2017) - Guzman, Marco; Laukkanen, Anne-Maria; Traser, Louisa; Geneid, Ahmed; Richter, Bernhard; Muñoz, Daniel; Echternach, Matthias
Abstract: Purpose: This study investigated the influence of tube phonation into water on vocal fold vibration. Method: Eight participants were analyzed via high-speed digital imaging while phonating into a silicon tube with the free end submerged into water. Two test sequences were studied: (1) phonation pre, during, and post tube submerged 5 cm into water; and (2) phonation into tube submerged 5 cm, 10 cm, and 18 cm into water. Several glottal area parameters were calculated using phonovibrograms. Results: The results showed individual differences. However, certain trends were possible to identify based on similar results found for the majority of participants. Amplitude-to-length ratio, harmonic-to-noise ratio, and spectral flatness (derived from glottal area) decreased for all tube immersion depths, while glottal closing quotient increased for 10 cm immersion and contact quotient for 18 cm immersion. Closed quotient decreased during phonation into the tube at 5 cm depth, and jitter decreased during and after it. Conclusion: Results suggest that the depth of tube submersion appears to have an effect on phonation. Shallow immersion seems to promote smoother and more stable phonation, while deeper immersion may involve increased respiratory and glottal effort to compensate for the increased supraglottal resistance. This disparity, which is dependent upon the degree of flow resistance, should be considered when choosing treatment exercises for patients with various diagnoses, namely hyperfunctional or hypofunctional dysphonia.